Pengaruh Kegiatan Paper Quilling terhadap Keterampilan Motorik Halus Anak Usia 5-6 Tahun di TK Negeri Pembina - Cahyani, Rheina; Herlina, Hj; Hidayah, Sitti Nur (AS-SABIQUN, 2024)
The aim of this research is to find out the effect of paper quilling training on the abilities of children aged 5 and 6 years at the Pembina State Kindergarten. The research strategy used is a quantitative strategy with a Quasi Experimental Design research type. The population of this study were children attending the Pembina State Kindergarten aged between five and six years. Purposive sampling was used as sample collection in this research. The sample consisted of 28 children, 14 children were in the experimental group and 14 children were in the control group. Descriptive and non-parametric statistical analysis is the data collection method used. Considering that the results of the two-tailed data analysis were 0.001 < 0.05, H1 was accepted and Ho was rejected, this shows that there has been an increase in fine motor skills in children at the Pembina State Kindergarten.